Over there in the air : the fightin' Texas aggies in World War I, 1917-1918 - Adams, John A., Jr., 1951- (Texas A & M University Press, 2020)
""Over There in the Air" tells the little-known story of the contribution of Texas A & M University to early aviation in World War I"-- Provided by publisher
Keywords: Texas A & M University -- Students.; Texas A & M University -- Alumni and alumnae -- History.; Texas A & M University; Soldiers -- United States.; Military education -- Texas.; Air pilots, Military -- Texas -- Biography.; World War, 1914-1918 -- Aerial operations.; Pilotes d'aéronef militaires -- Texas -- Biographies.; Guerre mondiale, 1914-1918 -- Opérations aériennes.; History / United States / State & Local / Southwest (AZ, NM, OK, TX); History / Military / Aviation.; History / Military / World War I.; Military education; Soldiers; Students; Universities and colleges -- Alumni and alumnae; Texas; United States; Electronic books.; History; Biographies.